PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GUIDED NOTE TAKING DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 23 PADANG TAHUN PELAJARAN 2013/2014 - Lisa Herman, Rahma; Febriana, Rina; Melisa, Melisa (Pendidikan Matematika, 2014)
ABSTRACTÂ The background of this research was the lack of students understanding mathematical concept, the students didnât attentions for teacher explanation and lacke students noted the subject describes teachers. The purpose of this research is to knows students understanding in mathematical concept with applying active learning strategy by using guided note taking with quiz to be better from the student mathematical concept with apply the conventional learning at grade eighth of SMPN 23 Padang of academic 2013/2014 years. This research is experimental research with the random design of subject. The population is the students grade eight of SMP 23 Padang of academic 2013/2014 years. The sample has to with randomly that choosen grade VIII1 has experimental class and VIII2 has control class. The instrument are quiz and test. The type of test is essay with reliabilitas test is 0,86. The analyze technique of the data using one side test t with software MINITAB. Based on analyze of the data to the real Â Î±=0,05 the result P-value = 0,008. P-value Â is less than from Î±= 0,05, so the hypothesis of the research will accept, that mean is the understanding of students mathematical concept with apply active learning strategy by using guided note taking with quiz is better from the students understanding mathematical concept with apply conventional learning at grade eighth of SMPN 23 Padang.